1999
DOI: 10.1055/s-2007-1013100
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Therapy of Fulminant Pulmonary Embolism: Early and Late Results

Abstract: Pulmonary embolectomy on cardiopulmonary bypass remains an adequate therapy in patients with failure of or contraindication to thrombolysis, and HIT is not a contraindication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 16 publications
(27 reference statements)
0
16
0
2
Order By: Relevance
“…[2,3] On the other hand, with rapid diagnosis, careful patient selection, and improved surgical techniques, high survival rates of 89% at 10 months have been achieved. [24] Debates continue regarding whether or not the complexity of the surgical procedure is worth the risk and whether there are enough postoperative care facilities that have sufficient experience to care for patients who undergo this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] On the other hand, with rapid diagnosis, careful patient selection, and improved surgical techniques, high survival rates of 89% at 10 months have been achieved. [24] Debates continue regarding whether or not the complexity of the surgical procedure is worth the risk and whether there are enough postoperative care facilities that have sufficient experience to care for patients who undergo this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The operative mortality rate for a surgical embolectomy is stated to be 20-50% because it is usually performed on moribund patients and is often followed by prolonged resuscitation. [2,3] Because of this, a surgical embolectomy is seldom performed today, even though it is a viable option for the management of these patients. On the other hand, a surgical embolectomy performed in cases of APE has also been stated to reduce the progression to chronic thromboembolic pulmonary hypertension (CTPHT).…”
mentioning
confidence: 99%
“…Unfortunately, the risk of surgical treatment for PE remains high. A recent study reported the perioperative mortality rate of pulmonary embolectomy to be 29% (15). We chose to treat this patient with systemic thrombolysis rather than subject him to the risk of thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Right ventricular dysfunction, assessed by echocardiography, has been shown to be an independent predictor of mortality. 9 Therapy options include heparin therapy (low molecular-weight heparins showing some advantages 10 ), warfarin therapy, caval filters, 11 thrombolysis with no one lytic agent showing superiority, 12 surgical embolectomy 13 and catheter embolectomy. 14 New catheter technologies might make this the treatment of choice in the future.…”
Section: Discussionmentioning
confidence: 99%